Communication Challenges with Children and Young People - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
Although human communication can be described by a number of general characteristics, it is influenced by a several changing circumstances, such as the external social environment, the prevailing culture, and norms and rules. Their effects exist through human actors, who are the most important actors in the communication process. But the people who play a major role in the interaction alsohave characteristics that directly or indirectly influence the way they communicate and the concrete forms of reactions. Age is such a determining element. Communication skills can also differ significantly depending on mental and psychological abilities that change with age. Thus, we face different characteristics and problems when communicating with children or even the elderly, due to changes in biological characteristics (such as hearing) or cognitive abilities. In addition to presenting the main communication attitudes of the new generation of children living in the 21st century, the chapter pays special attention to the overview of the communication skills of young people who come into conflict with the law. This is particularly important because in the case of young people in the moral danger zone, these problems (such as language developmental disabilities) can be a significant obstacle to exercising their rights as children.Keywords: iGeneration, communication skills, DLD (development language disorder), children communication, good practice, communication problems and psychological, mental, or psychiatric characteristics,language or communication difficulties, youth offenders